2021
DOI: 10.3389/fmars.2021.754789
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microplastics on the Bioenergetics of the Mussel Mytilus coruscus Assessed by Cellular Energy Allocation Approach

Abstract: Marine microplastics pollution is a major environmental concern in marine ecosystems worldwide, yet the biological impacts of microplastics on the coastal biota are not yet fully understood. We investigated the impact of suspended microplastics on the energy budget of the mussels Mytilus coruscus using the Cellular Energy Allocation (CEA) approach. The mussels were exposed to control conditions (no microplastics) or to one of the three concentrations of 2 μm polystyrene microspheres (10, 104, and 106 particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…The lower activity of this key enzyme for beta-oxidation of fatty acids may be prognostic of metabolism disorders and energy reserves mobilization: while limited effects were caused by PEST-MFs, both PA and CO determined a relevant decrease of neutral lipids after the recovery phase, with a particularly relevant magnitude of variation in PA-treatment compared to the exposure phase. In this respect, since neutral lipids are one of the main energy reserve in bivalves (Bocchetti and Regoli, 2006), the observed decrease may reflect a demand to sustain the activated stressdefense mechanisms (Shang et al, 2021), or an inefficient nutrients assimilation deriving from MFs presence in the digestive tissue, as previously hypothesized for MPs (Wright et al, 2013;Trestrail et al, 2021).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The lower activity of this key enzyme for beta-oxidation of fatty acids may be prognostic of metabolism disorders and energy reserves mobilization: while limited effects were caused by PEST-MFs, both PA and CO determined a relevant decrease of neutral lipids after the recovery phase, with a particularly relevant magnitude of variation in PA-treatment compared to the exposure phase. In this respect, since neutral lipids are one of the main energy reserve in bivalves (Bocchetti and Regoli, 2006), the observed decrease may reflect a demand to sustain the activated stressdefense mechanisms (Shang et al, 2021), or an inefficient nutrients assimilation deriving from MFs presence in the digestive tissue, as previously hypothesized for MPs (Wright et al, 2013;Trestrail et al, 2021).…”
Section: Discussionmentioning
confidence: 68%
“…Despite their emerging widespread abundance and predominance in biota, our knowledge on the molecular and cellular effects of MFs is still limited; indeed, a great effort has been carried out in the context of microplastics (i.e. Avio et al, 2015;Paul-Pont et al, 2016;Ribeiro et al, 2017;Barboza et al, 2018;Pittura et al, 2018;Tang et al, 2020;Missawi et al, 2021;Shang et al, 2021;Trestrail et al, 2021;Romdhani et al, 2022), but typically without considering microfibers, certainly not the natural and semi-synthetic ones. Among the available literature, dimensional characteristics of MFs have shown to influence their ingestion and biological effects: a preferential ingestion of MFs of 100-250µm was observed in the Asian clam exposed to PEST MFs for 2 days at a concentration of 1000 items L-1 (Li et al, 2019), and length dependent effects were observed in Mytilus galloprovincialis with harsher genotoxic damages caused by 100 µm long PET-MFs compared to smaller ones (Choi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some unique patterns were identi ed in the mantle, such as "carbohydrate transport and metabolism", which was signi cantly enriched among upregulated genes in the 0.025 µg L -1 condition and may be linked with the low glycogen level measured in oyster muscle. A depletion of cellular energy stores (carbohydrates, lipids and proteins) has previously been demonstrated in mussels exposed to micro-PS 34 . The early depletion of glycogen is consistent with its role as a rapidly mobilizable metabolic fuel used to cover a rapid increase in energy demand in bivalves 34 .…”
Section: Discussionmentioning
confidence: 72%
“…Whilst behavioural changes were only recorded for S. plana, both species exhibited a significant reduction in protein content as a result of exposure to 5% sedimentary tyre particles, which translated into a reduction in energy reserves for H. diversicolor. A reduction in the protein content of marine invertebrates has been recorded in other sedimentary microplastic exposure experiments; Bour et al (2018) found a significant decrease in protein content in the burrowing bivalves Abra nitida and Ennucula tenuis in response to exposure to large (125-500 μm) PE microparticles, leading to a significant decrease in energy reserves in E. tenuis, whilst Shang et al (2021) found exposure to microplastics resulted in a reduction in all cellular energy stores (proteins, lipids and carbohydrates) in the mussel Mytilus unguiculatus (previously M. coruscus) in response to 2 μm diameter polystyrene spheres.…”
Section: Energy Reservesmentioning
confidence: 63%